RESOURCE CLASSROOM AS A MODEL FOR ORGANIZING INCLUSIVE EDUCATION IN THE RUSSIAN FEDERATION - Bliznyuk, Olga; Senchenkov, Nikolay (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
On the basis of inclusive education importance for children with disabilities and special educational needs, which contributes to the development of communication and socialization skills, as well as the development of tolerance among typically developing children, the aim of this work was to describe a resource classroom as a model for the effective organization of inclusive education in mainstream schools of the Russian Federation. The article defines a resource classroom in Russian educational system. The authors determine legal and regulatory frameworks to establish such classrooms. This study presents the main methodological base of resource classrooms, the organization for the educational process and space according to the students needs. Based on the generalization for the experience of the resource classrooms in the regions of the Russian Federation, the interaction for all elements of this model is shown. The study confirms that positive learning outcomes, involvement and inclusion of children with disabilities and special educational needs in a mainstream school and society are the evidence for the effectiveness of resource classrooms. The described model makes inclusion in education comfortable and effective not only for students of the resource classroom, but also for typically developing children, parents and the teaching staff of a school.